Design of rapamycin and resveratrol coloaded liposomal formulation for breast cancer therapy - Reis, Leidiana Rocha dos [UNESP] (2023)
Aims: The development of rapamycin (RAP) and resveratrol (RSV) coloaded liposomes (RAP-RSV-LIP) for breast cancer therapy. Materials & methods: Liposomes were prepared using a high-pressure homogenization technique and evaluated according to their physicochemical characteristics, cellular uptake and cytotoxicity against tumoral and normal cells. Results & conclusion: The RAP-RSV-LIP showed negative surface charge, size around 100 nm, low polydispersity and high encapsulation efficiency for RAP and RSV (58.87 and 63.22%, respectively). RAP-RSV-LIP showed great stability over 60 days and a prolonged drug release profile. In vitro studies indicated that RAP-RSV-LIP were internalized in an estrogen receptor-positive human breast cancer cell line (MCF-7, 34.2%) and improved cytotoxicity when compared with free drugs. Therefore RAP-RSV-LIP showed great antitumoral potential against breast cancer cells.